Analysis of Halal Awareness and Free Halal Certification Services on the Interest of Micro, Small, and Medium Enterprises (MSMEs) in Obtaining Halal Certificates (A Study at the Ministry of Religious Affairs, Yogyakarta City) - Tuti Mulyani; Heri Prasetyo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study purposes to analyze the influence of Halal Awareness and free halal certification services (SEHATI) on the interest of Micro, Small, and Medium Enterprises (MSMEs) in obtaining halal certification in Yogyakarta City. The examination utilized a quantitative approach with 100 MSME respondents. Data were gathered through questionnaires and interpreted using multiple linear regression with SPSS software. The outcome demonstrates that Halal Awareness has a positive and significant partial effect on MSME interest, suggesting that understanding the importance of halal products enhances their willingness to pursue halal certification. Additionally, SEHATI services also have a positive and significant partial impact, demonstrating that this program successfully addresses cost and technical barriers previously faced by business actors. Simultaneously, these two variables significantly contribute to increasing MSME interest in obtaining halal certification, with SEHATI services having a more dominant influence. This study concludes that a combination of internal halal awareness and external support, such as SEHATI services, can enhance MSME participation in halal certification. It is recommended that related institutions expand socialization efforts and simplify access to the program, while future research could broaden the scope of regions and variables to provide more in-depth insights.